2001
DOI: 10.7863/jum.2001.20.12.1365
|View full text |Cite
|
Sign up to set email alerts
|

Use of three‐dimensional ultrasonography for prenatal diagnosis of ambiguous genitalia.

Abstract: ex identification is one of the prime expectations of any parent during the prenatal ultrasound examination. However, the ability to visualize fetal genitalia not only has important social implications but also has considerable medical implications. Various endocrine disorders and complex genitourinary malformations can be manifested in the form of anomalous genitalia, and a delay in diagnosis may lead to an increase in postnatal morbidity and mortality.1 In addition, correctly identifying and illustrating maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Cheikhelard et al (2000) reported an accuracy of 100% in male and 46% in female fetuses in the prenatal diagnosis of abnormal genitalia. Currently, 3D ultrasound has become a useful tool for evaluation of ambiguous genitalia (Naylor et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Cheikhelard et al (2000) reported an accuracy of 100% in male and 46% in female fetuses in the prenatal diagnosis of abnormal genitalia. Currently, 3D ultrasound has become a useful tool for evaluation of ambiguous genitalia (Naylor et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, Cafici and Iglesias 5 concluded that 3D sonography does not facilitate the diagnosis in cases of hypospadius, but it does aid in explaining the findings to the family. Naylor et al 4 concluded that 3D sonography "both correctly identified and visually clarified" the diagnosis in a case of ambiguous genitalia; however, in both of these previous cases, the fetal karyotype was known to be 46,XY before the sonographic evaluation. Most recently, a study by Verwoerd-Dikkeboom et al 6 reported that 3D sonography was incorrect in diagnosing 2 of 3 cases of ambiguous genitalia.…”
Section: To the Editormentioning
confidence: 99%
“…These techniques are particularly useful for examining subtle external features in fetuses at risk of anomalies or in fetuses found to have a congenital malformation. As this is such a new technique there is relatively little published describing the applications in terms of diagnosis of ambiguous genitalia [50]. The 3‐dimensional appearance of normal male development at 16 and 23 weeks of gestation is shown in Fig.…”
Section: Three‐dimensional Usmentioning
confidence: 99%